Nomophobia and smartphone addiction among college students - Fuady, Ikhsan; Wibowo, Kunto Adi; Sutarjo, Moch Armien Syifaa (The International Journal of Politics and Sociology Research, 2024)
The use of smartphones creates problems of nomophobia and addiction among the younger generation. This study aims (a). to determine the effect of fear of not being able to communicate on smartphone addiction among students; (b). to determine the effect of fear of losing connectedness on smartphone addiction among students; (c). to determine the effect of fear of not being able to access information on smartphone addiction among students; and (d). to determine the effect of fear of not being able to communicate on smartphone addiction among students. This research is designed as a quantitative research with a survey approach. The population of this research is undergraduate students in West Java, while the sampling technique of this research is convenience sampling, and with a sample size of 123 samples. The research data were analyzed using descriptive and inferential statistical tests using multiple linear regression tests. The results showed that overall the fear of not having a smartphone affects smartphone addiction among students. The nomophobia factors that influence dating include the fear of losing connectedness and the fear of losing convenience.